THE ROLE OF MANAGEMENT IN THE SUCCESSFUL ORGANISATION OF CONFERENCES: A CASE STUDY OF HOLIDAY INN MUNICH CITY CENTRE - Bjelić, Katarina; Jarman, Darren; Kuhn, Sebastian; Vujko , Aleksandra (The Business of Tourism, 2025)
This paper explores the role of management in the successful organisation of a conference, with a particular focus on industry events, known as the MICE industry. The terms and importance of the MICE industry are defined, as well as its impact on the competitive advantage of hotels. The paper presents a case study of the Holiday Inn hotel in Munich, which is part of the international hotel chain IHG (InterContinental Hotels Group). The IHG standards and characteristics of the Holiday Inn hotel were analyzed, with special reference to the organisation of events within the hotel. The paper examines in detail the process of organising events at the Holiday Inn hotel, emphasizing the key role of management in this process. Special attention is paid to the policy and set of values ​​that event managers must follow in order to ensure the successful organisation of the conference. Also, the paper analyzes how management can contribute to the creation of competitive advantages through effective planning, communication and execution of conference events, thereby increasing client satisfaction and guest loyalty. In this context, the application of strategic management and project management facilitates the integration of long-term objectives with day-to-day operations, thereby ensuring efficient and successful management of all aspects of event organisation.
Keywords: event management; management efficiency; strategic management and project management; banquet organisation; Holiday Inn Munich City Centre; Intercontinental Hotels Group